Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1002/ijc.2910470622
|View full text |Cite
|
Sign up to set email alerts
|

Expression of dipeptidyl aminopeptidase IV during enterocytic differentiation of human colon cancer (Caco‐2) cells

Abstract: The human colon cancer cell line Caco-2 spontaneously differentiates to an enterocyte-like cell after confluence under standard culture conditions. This is characterized by polarization of the cell monolayer with the appearance of tight junctions, a brush border membrane and expression of brush-border-membrane-associated hydrolases. Studies have shown that differentiated Caco-2 cells express relatively high levels of dipeptidyl aminopeptidase IV (DPP IV) when compared with other enzymes. However, the biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Previous studies from our group have shown that: (a) up-regulation of KGFRs can be observed in human primary cultured keratinocytes during in vitro differentiation induced by high Ca 2þ concentrations (Marchese et al, 1997) and (b) the confluence-induced differentiation of the non-transformed human keratinocyte cell line HaCaT causes an increase of functional KGFRs on the plasma membranes of the suprabasal cells which appears related with retention of the proliferative activity (Capone et al, 2000). Here we report that also for the intestinal epithelial cell line Caco-2, a widely used in vitro model of intestinal proliferation and differentiation (Chantret et al, 1988;Yoshioka et al, 1991), as well as of brush border assembly (Peterson and Mooseker, 1993), the expression of KGFRs is up-modulated during the initial spontaneous differentiation of the cells, as shown by the results obtained either from the biochemical Western blot detection of the total KGFR protein or from the immunofluorescence and immunoelectron microscopic analysis of the expression and distribution of the receptors on the cell plasma membranes (Fig. 8).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies from our group have shown that: (a) up-regulation of KGFRs can be observed in human primary cultured keratinocytes during in vitro differentiation induced by high Ca 2þ concentrations (Marchese et al, 1997) and (b) the confluence-induced differentiation of the non-transformed human keratinocyte cell line HaCaT causes an increase of functional KGFRs on the plasma membranes of the suprabasal cells which appears related with retention of the proliferative activity (Capone et al, 2000). Here we report that also for the intestinal epithelial cell line Caco-2, a widely used in vitro model of intestinal proliferation and differentiation (Chantret et al, 1988;Yoshioka et al, 1991), as well as of brush border assembly (Peterson and Mooseker, 1993), the expression of KGFRs is up-modulated during the initial spontaneous differentiation of the cells, as shown by the results obtained either from the biochemical Western blot detection of the total KGFR protein or from the immunofluorescence and immunoelectron microscopic analysis of the expression and distribution of the receptors on the cell plasma membranes (Fig. 8).…”
Section: Discussionmentioning
confidence: 92%
“…The other agents tested in this study, 13-cis-retinoic acid and 4-hydroxyphenretanimide, were effective in inhibiting the formation of aberrant crypts, with 13-cis-retinoic acid being the much more effective compound. Both in cell culture and in a wide variety of animal tissues 13-cis-rctinoic acid is a powerful differentiating agent (De Luca, 1991;Yoshioka et al, 1991). It has bcen shown to inhibit cancer in the rat colon, but its effects in the human colon have not been directly tested (O'Dwyer et al, 1987).…”
Section: Discussionmentioning
confidence: 97%
“…IgE binding epitopes are widely spread all along the -lactoglobulin and -lactalbumin molecules as evidenced by using tryptic and synthetic peptides or overlapping peptides. The best recognized peptides, by more than 90% of the patients, are BLG fragments (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), and (149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160)(161)(162), each of them accounting for 10 to 15% of whole BLG immunoreactivity [147]. In addition the C-terminal fragment (149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160)…”
Section: Allergenic Constituents Of Foods and Allergenic Structures (mentioning
confidence: 99%
“…DPP IV is synthesized within the cell as a dimeric glycoprotein and is subsequently integrated in the apical cell membrane (brush border), with its active site being situated in the gut lumen [56]. Thus DPP IV activity can be measured without prior cell lysis, simply by adding a specific substrate, e.g.…”
Section: Assessment Of Effects On Epithelial Functions Of Cultured Inmentioning
confidence: 99%